Abnormal Outer Choroidal Vasculature in Amblyopia - Noriko Terada; Manabu Miyata; Yuki Muraoka; Masayuki Hata; Masahiro Fujimoto; Satoshi Yokota; Hideo Nakanishi; Kenji Suda; Munemitsu Yoshikawa; Sotaro Ooto; Hiroshi Ohtsuki; Akitaka Tsujikawa (Journal of Ophthalmology)
Purpose. Several studies have indicated morphological changes in the choroid in amblyopia cases. This study investigates whether choroidal vasculature was different among amblyopic and fellow eyes in unilateral amblyopia patients and healthy eyes, using en face images acquired via swept-source optical coherence tomography (SS-OCT). Design. Prospective, observational case-control study. Methods. This study included 14 consecutive patients with unilateral amblyopia and 22 age- and axial length-matched healthy eyes. Using SS-OCT, we obtained en face images of choroidal vasculature midway through the subfoveal inner and total choroid, corresponding to the vasculature of the choriocapillaris and Sattler’s layer (inner choroid) and Haller’s layer (outer choroid), respectively. We analyzed the en face images of the inner and outer choroidal vascular areas in 3 × 3 mm squares adjusted from 6 × 6 mm squares, using Littmann’s magnification correction, after binarization of the images as a portion of the whole area. Results. The outer choroidal vascular areas were larger in both amblyopic and fellow eyes than in healthy eyes (both P<0.001), although there were no significant differences in inner (56.35 ± 2.46% and 56.27 ± 3.75%, respectively) or outer (61.49 ± 4.95% and 61.48 ± 3.73%, respectively) choroidal vascular area between amblyopic and fellow eyes (P=0.98  and  0.91, respectively). An outer choroidal vascular area of 59% was set as an appropriate cutoff value for distinguishing patients from controls. Conclusions. The outer choroidal vascular area was larger in both amblyopic eyes and fellow eyes compared to healthy eyes. Our findings may help clarify the etiology of amblyopia.